FINANCIAL ANALYSIS OF COMPANY VALUE IN PROPERTY COMPANIES ON INDONESIA STOCK EXCHANGE FROM 2017 TO 2019 - Setyani Sri Haryanti; Irwan Christanto Edy (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This study aims to analyze the company value of companies engaged in property on the Indonesia Stock Exchange with financial ratios. The population in this study are all companies engaged in the property sector, which are already listed on the Indonesia Stock Exchange . The sample used was 37 property companies that have been listed on the Indonesia Stock Exchange from 2017 to 2019. The sampling technique used purposive sampling technique. This study used secondary data, an analysis tool with Multiple Linear Regression. Financial analysis using profitability ratios as measured by return on asset, liquidity ratio by Cash Ratio, Solvency ratio by debt ratio, while the company value using Toben's Q. Results hypothesis testing proved that the profitability ratio and solvency ratio showed positive and significant effect to company value . The liquidity ratio shows negative and insignificant effect to company value . The results of the F test prove that the profitability ratio, liquidity ratio and solvency ratio together have a significant effect to company value. The test results of determination prove that the overall impact that the independent variable on the dependent variable of 17.1% while the remaining 82.9 % is influenced by variables or other models that are not included in this study